(untitled) (Journal of Rangpur Medical College, 2023)
Background: The burden of having small for gestational age (SGA) children is high in low- and middle-income countries, mainly in South Asia. Identifying these low birth weight and SGA infants and referring them to higher centers for effective intervention will help reduce neonatal mortality and morbidity. Anthropometric measurements of the neonatal population, especially birth weight measurements, constitute an important scientific research tool for studying the determinants and consequences of impaired or excessive fetal growth. Objective: To find an alternative anthropometric procedure, the present study was done to measure and compare birth weight with crown heel length (CHL), head circumference (HC), and mid-upper arm circumference (MUAC) as predictors of birth weight in small for gestational age (SGA). Methods: This cross-sectional, analytical study was done in the Department of Anatomy, Rangpur Medical College, Rangpur from July 2020 to June 2021 on 200 newborns of both sexes with gestational age between 37 and 42 weeks. The newborn was selected and measured within 24 hours of birth. 100 term newborns weighted <2.5 kg regarded as SGA were the subjects of the study. Another 100-term newborns weighted >2.5 kg regarded as AGA served as control. The birth weight, head circumference, mid-upper arm circumference, and crown heel length were measured and a comparison of all the variables was done between AGA and SGA newborns. Data was analyzed by using a statistical package for social sciences (SPSS version 26). Result: The mean± SD of birth weight in AGA and SGA groups was 2.99 ±0.31 and 2.10±0.24 respectively; it was observed that the mean± SD of crown heel length, head circumference, and mid-upper arm circumference and Ponderal index in AGA group was significantly higher than SGA group; however the MAC/HC ratio was almost similar between AGA and SGA groups. All the above variables were significantly correlated with birth weight in both AGA and SGA groups. Conclusion: Some simple and inexpensive measurements of newborns especially the head circumference of SGA newborns are as effective as birth weight measurement; crown heel length, and mid-upper arm circumference could also be used to predict birth weight in SGA newborns. J Rang Med Col. September 2023; Vol. 8, No. 2: 14-19